Feature Extraction of a Non-Stationary Seismic–Acoustic Signal Using a High-Resolution Dyadic Spectrogram - Diego Seuret-Jiménez; Eduardo Trutié-Carrero; José Manuel Nieto-Jalil; Erick Daniel García-Aquino; Lorena Díaz-González; Laura Carballo-Sigler; Daily Quintana-Fuentes; Luis Manuel Gaggero-Sager (Sensors, 2023)
Using a novel mathematical tool called the <semantics>Te</semantics>-gram, researchers analyzed the energy distribution of frequency components in the scale–frequency plane. Through this analysis, a frequency band of approximately 12 Hz is identified, which can be isolated without distorting its constituent frequencies. This band, along with others, remained inseparable through conventional time–frequency analysis methods. The <semantics>Te</semantics>-gram successfully addresses this knowledge gap, providing multi-sensitivity in the frequency domain and effectively attenuating cross-term energy. The Daubechies 45 wavelet function was employed due to its exceptional 150 dB attenuation in the rejection band. The validation process encompassed three stages: pre-, during-, and post-seismic activity. The utilized signal corresponds to the 19 September 2017 earthquake, occurring between the states of Morelos and Puebla, Mexico. The results showcased the impressive ability of the <semantics>Te</semantics>-gram to surpass expectations in terms of sensitivity and energy distribution within the frequency domain. The <semantics>Te</semantics>-gram outperformed the procedures documented in the existing literature. On the other hand, the results show a frequency band between 0.7 Hz and 1.75 Hz, which is named the planet Earth noise.